Escolhas criativas e humor: estudo de caso da sitcom televisiva inglesa The Office - Patané, Willy Nielsen (2016)
The present research aims to explain, based on humor theories, the reasons why the embarrassing scenes on the British television sitcom The Office can be considered funny. The show, which did not have a big amount of jokes, became a hit around the world, showing extremely embarrassing situations occurred inside a (fictitious) paper company factory office. Describing the peculiarities of the show and the writer s creative choices has also been one of the research s purposes. Therefore, the study was based on themes such as: sitcoms, humor and embarrassment. The hypotheses were that portray the silence and explore the characters reactions would be one of the show s features. The relief felt by the viewers, once they're not on the characters shoes, and the shock they might feel watching the awkward scenes and actions captured by the camera were some of the reasons that might make the audience find funny the embarrassing situations. Methodologically, the research has been a qualitative, descriptive and documental study. Episodes and scripts of the series, as well as materials and testimonials about the show, have been analyzed. The methodological basis has been composed of works by: Mills (2008; 2011), Evans (2001), Fox (2014) and Helitzer and Shatz (2005) about sitcom and comedy writing; Berger (1993), Propp (1992), Fox (2014) and Mills (2011) about humor; Lewis (1995) and Miller (1987; 1995) about embarrassment. The conclusion is that creating a "painful" show and making it seems like a real documentary have been some of the choices made by the sitcom's writers. It has also been found that the conflicts portrayed on the scenes, the main character s flaws, the incongruity between what people expect from an office's boss and the misplaced attitudes of this character, added to the sense of superiority experienced by the viewer, were some of the details that might explain why the office can be considered a funny show